Evaluation of the biodeterioration activity of lichens in the Cave Church of Üzümlü (Cappadocia, Turkey). (February 2018) - Casanova Municchia, Annalaura; Bartoli, Flavia; Taniguchi, Yoko; Giordani, Paolo; Caneva, Giulia
Abstract: The Üzümlü Church is an unusual soft tuff formation located in central Turkey (Cappadocia) dated around the 7th century. The rocks on its external surfaces show a severe erosion with an evident surface detachment. Moreover, the widely distributed black-grey crusts mainly consisting of lichens point out the need of evaluating their deteriorative effects. This research was focused on lichen deterioration by indicating the biodeterioration processes and on selecting the most appropriate preservation treatments suitable for stone conservation. The interaction of lichens with stone was studied by evaluating through microscopic analyses, the spread and the depth of fungal hyphae penetration, and by applying the LPBA Index. The SEM analysis of all fragments shows a dramatic loss of the stone matrix and a dense network of fungal hyphae within the rock. Nevertheless, both the high penetration of fungal hyphae, and the consequent difficulty in their removal without a strong peeling effect, both the relevant loss of the stone matrix and finally the evident reduction of water penetration when crusts are present in the surfaces, advise against their removal. Further chemical treatments of consolidation should be carefully evaluated. Highlights: Study of the Üzümlü Church in order to detect the biodeterioration processes. Evaluating by microscopic analyses of the lichens interaction. A considerable physical and chemical deterioration occurs in each sample. Detection of a bio-mobilization of several elements from the interior of the rock.